A Representative of the People: A review of Dominic Burbidge’s An Experiment in Devolution: National Unity and the Deconstruction of the Kenyan State - Kibira, Lizzy Muthoni (Strathmore Law Journal, 2021)
This article is dedicated to analyze Dominic Burbidge’s An experiment in devolution. Published by Strathmore University Press in 2019, the 319-page volume is a welcome addition to the growing scholarship on devolution in Kenya. This text, indeed, brings with it a much needed ‘empirical grit’ to a discourse previously saturated with historically and theoretically derived conjecture. The hallmark of the book is, therefore, this attention to the material, the meticulousness with which it relays empirical findings and finally, how the author manages to successfully marry empirical data and theory; resulting in an interesting telling of the story of devolution. Thus, Burbidge sets out to test the performance of devolution in the counties where it was most predicted to fail: the former Central Province. He investigates how devolution has actually played out in this region; taking into consideration the historically complicated relationship between Mount Kenya and Nairobi and the enduring scepticism as to the compatibility of devolution and the interests of Central Kenya.